Effects of an integrated intervention program for alcoholism (IIPA) on learning, memory and quality of life (QOL) in persons with alcohol dependence at the Centre for Addiction Medicine, Bengaluru, India - Rajesh Kumar; Keshav J. Kumar; Vivek Benegal; Bangalore N. Roopesh; Girikematha S. Ravi (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - This study aims to examine the effectiveness of an integrated intervention program for alcoholism (IIPA) for improving verbal encoding and memory, visuospatial construction, visual memory and quality of life (QoL) in persons with alcohol dependence. Design/methodology/approach - The sample comprised treatment-seeking alcohol-dependent persons (n = 50), allotted into two groups: (1) the treatment as usual (TAU) group (n = 25) and (2) the treatment group (n = 25)]. The groups were matched on age (±1 year) and education (±1 year). The TAU group received standard pharmacological treatment, psychotherapeutic sessions on relapse prevention and yoga for 18 days, while the treatment group received IIPA sessions in addition to the usual treatment. Auditory verbal learning test, complex figure test and QoL scale were administered at pre- and post-treatment along with screening measures. Findings - The two groups were comparable on demographic variables, clinical characteristics and outcome measures at baseline. Pre- to post-treatment changes (gain scores) comparison between the treatment and TAU groups revealed a significant difference in verbal encoding, verbal and visual memory, verbal recognition, visuospatial construction and QoL. Research limitations/implications - This study suggests that IIPA is effective for improving learning and memory in both modality (verbal and visual) and QoL in persons with alcoholism. The IIPA may help in better treatment recovery. Practical implications - The IIPA may help in treatment for alcoholism and may enhance treatment efficacy. Originality/value - IIPA is effective for improving learning and memory in both modalities and QoL in persons with alcohol dependence. The IIPA may help in better treatment recovery.